THE PROCESS OF ACHIEVING THE SELF ARCHETYPE FROM THE PERSPECTIVE OF ANALYTICAL PSYCHOLOGY (TOWARDS UNDERSTANDING THE CONCEPT OF GOD-MAN) - VAJDOVÁ, Ivana Ryška (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2016)
The Process of Achieving the Self Archetype from the Perspective of Analytical Psychology (Towards Understanding the Concept of God-Man). This article is dedicated to Jung’s notion of the individuation process which is inseparable from his idea of Soul as a harmonious and dynamic wholeness of self. The individuation process pursues its own objectives and places specific demands on human being in a course of his or her life. Ultimately it tries to integrate different components of soul – the complexes – into one organic unit. The individuation process manifest itself as spontaneous vital activity but generally it is a very problematic and enigmatic phenomenon because it raises from confrontation between outside and inside influences of human Psyche. This article also puts emphasis on Jung’s notion of God-Man. REZUMAT: Procesul dobândirii arhetipului sinelui din perspectiva psihologiei analitice (spre înţelegerea conceptului de Dumnezeu-Om). Studiul de faţă este dedicat noţiunii de proces de individuare a lui Jung, care nu poate fi despărţită de concepţia sa cu privire la suflet ca un întreg armonios şi dinamic al sinelui. Procesul de individuare urmează propriile sale obiective şi îl confruntă pe om cu cerinţe specifice de-a lungul vieţii sale. În ultimă instanţă, el încearcă să integreze diferitele componente ale sufletului – complexele – într-o unitate organică. Procesul de individuare se manifestă ca o activitate spontană vitală, dar este în general un fenomen foarte problematic şi enigmatic, deoarece apare din confruntarea influenţelor interne şi externe ale psihicului uman. Articolul accentuează de asemenea noţiunea de Dumnezeu-Om a lui Jung. Cuvinte cheie: individuare, arhetipuri, ego, sine, Dumnezeu-Om, psihologie analitică, nevroză, C. G. Jung